The outstanding organization : generate business results by eliminating chaos and building the foundation for everyday excellence - Martin, Karen (McGraw-Hill, 2012)
Winner of The Shingo Research and Professional Publication Award! After two decades in the trenches of helping companies design and build better, more efficient operations, Karen Martin has pinpointed why performance improvement programs usually fail: Chaos, the sneaky but powerful force that frustrates customers, keeps business leaders awake at night, and saps company morale. In The Outstanding Organization, Karen offers a toolbox for combating chaos by creating the organizational conditions that will allow your improvement efforts to return greater gains. Proven, practical, and surprisingl.